PENGEMBANGAN MEDIA POCKET CARD UNTUK MENINGKATKAN MINAT BACA SISWA KELAS II MIS AL BASHIRAH (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop Pocket Card learning media to increase reading interest in second-grade students of MIS Al-Bashirah in the Indonesian language subject of antonyms. The type of research used is Research and Development (R&D) with the stages of analysis, design, development, and validation. Validation subjects consisted of material experts, media experts, and second-grade teachers of MIS Al-Bashirah. The research instruments were expert validation questionnaires and teacher response questionnaires. The material expert validation results obtained a score of 64 out of 75 or 85.3% (very appropriate category), media expert validation obtained a score of 67 out of 75 or 89.3% (very appropriate category), and teacher response obtained a score of 68 out of 75 or 90.6% (very appropriate category). Based on these results, it can be concluded that Pocket Card media is included in the very appropriate category for use as an Indonesian language learning medium for antonyms in second-grade elementary schools. This media is considered interesting, practical, and able to increase students' reading interest.